KOLOR JAKO ELEMENT KSZTAŁTOWANIA TOŻSAMOŚCI JEDNOSTKOWEJ I ZBIOROWEJ - Jurek, Krzysztof (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of this article is an attempt to analyze the function of color involving the shaping of personal and collective identity. Psychologists believe that colors emphasize human personality. Colors allow to express emotions and promote shared values. Symbols of color unite people, facilitate communication, strengthen social bonds and motivate to action. The author assumes that we live in a culture of images and color is one of the tools and methods of cognition of the social reality.